Evaluation of the effect of nicosulfuron at different times of application on the chemical component of maize (Zea mays) - Tari Tizhe; SAMSON O. ALONGE; DORA N. IORTSUUN; DAVID I. ADEKPE; KUCHELI BATTA (Smujo International, 2022)
Abstract. Tizhe TD, Alonge SO, Iortsuun DN, Adekpe DI, Batta K. 2022. Evaluation of the effect of nicosulfuron at different times of application on the chemical component of maize (Zea mays). Nusantara Bioscience 14: 122-127. This study aimed to evaluate the effect of nicosulfuron at different concentrations and times of application on the chemical compositions of maize (Zea mays L.) grain. A field experiment was conducted during the 2019 and 2020 cropping seasons. Furthermore, using a split-plot design, maize seed was planted; and four different concentrations of nicosulfuron (50, 100, 150, and 200 g/ha) were applied at 3, 5, and 7 Weeks After Sowing (WAS). The maize grain was analyzed using standard procedures for its proximate amino acids and mineral contents. The results showed that the different concentrations of nicosulfuron and its time of application significantly affected the proximate compositions except for the ash content. The 5 WAS application time had the significantly highest protein, crude fiber, and moisture content with 11.35, 2.60, and 12.01%, respectively, and the lowest carbohydrate (70.58%) and crude fat (2.33%). The nicosulfuron was observed to significantly affect all the amino acids and mineral (except on N) contents of the maize grain with 100 g/ha. This study recorded the significantly highest content of almost all the amino acids with 100 g/ha, and 50 g/ha was the lowest. The 5 WAS virtually had the highest amino acids, while the 3 WAS the lowest. Therefore, nicosulfuron and time of application both have a significant effect on the proximate amino acids and Mg and Ca components of maize grain. That means that using nicosulfuron at concentrations precisely above 100 g/ha and at a time other than 5 WAS negatively affects the chemical components of maize grain.